Improving Student Learning Outcomes in Theme 2 Always Saving Energy Through Problem Based Learning Models Assisted by Audio Visual Media in Class IV SD IT Darussalam Deli Tua - Lola Widia Sari Nasution; Sujarwo (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the Improvement of Student Learning Outcomes in Theme 2 Always Save Energy Through the Problem Based Learning Model Assisted by Audio Visual Media in Grade IV SD IT Darussalam Deli Tua. This research is a classroom action research (PTK) consisting of 3 cycles with 2 meetings in each cycle. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were teachers and 37 fourth grade students at SD IT Darussalam Deli Tua. Data collection techniques used test and non-test techniques in the form of tests, observation and documentation. Data analysis techniques consisted of qualitative and quantitative analysis. This classroom action research started from April to June 2023. This classroom action research was conducted at SD IT Darussalam, Deli Tua District. Student learning outcomes were measured through final tests, observations, and assessments from the groups. Data on student learning outcomes showed a significant increase after the application of the audio-visual-assisted Problem Based Learning model. It is known that in cycle III, where the learning was carried out for 2 meetings, 30 students who completed or 98% of the total number of students, namely 37 people, completed. This shows that student learning outcomes have reached indicators of success, namely students who achieve KKM 70 have reached 70% at the end of cycle III.